Phytochemical and Pharmacological Role of Liquiritigenin and Isoliquiritigenin From Radix Glycyrrhizae in Human Health and Disease Models - Ramalingam, Mahesh; Kim, Hyojung; Lee, Yunjong; Lee, Yun-Il (Frontiers in Aging Neuroscience, 2018)
The increasing lifespan in developed countries results in age-associated chronic diseases. Biological aging is a complex process associated with accumulated cellular damage by environmental or genetic factors with increasing age. Aging results in marked changes in brain structure and function. Age-related neurodegenerative diseases and disorders (NDDs) represent an ever-growing socioeconomic challenge and lead to an overall reduction in quality of life around the world. Alzheimer’s disease (AD) and Parkinson’s disease (PD) are most common degenerative neurological disorders of the central nervous system (CNS) in aging process. The low levels of acetylcholine and dopamine are major neuropathological feature of NDDs in addition to oxidative stress, intracellular calcium ion imbalance, mitochondrial dysfunction, ubiquitin-proteasome system impairment and endoplasmic reticulum stress. Current treatments minimally influence these diseases and are ineffective in curing the multifunctional pathological mechanisms. Synthetic neuroprotective agents sometimes have negative reactions as an adverse effect in humans. Recently, numerous ethnobotanical studies have reported that herbal medicines for the treatment or prevention of NDDs are significantly better than synthetic drug treatment. Medicinal herbs have traditionally been used around the world for centuries. Radix Glycyrrhizae (RG) is the dried roots and rhizomes of Glycyrrhiza uralensis or G. glabra or G. inflata from the Leguminosae/Fabaceae family. It has been used for centuries in traditional medicine as a life enhancer, for the treatment of coughs and influenza, and for detoxification. Diverse chemical constituents from RG have reported including flavanones, chalcones, triterpenoid saponins, coumarines, and other glycosides. Among them, flavanone liquiritigenin (LG) and its precursor and isomer chalcone isoliquiritigenin (ILG) are the main bioactive constituents of RG. In the present review, we summarize evidence in the literature on the structure and phytochemical properties and pharmacological applications of LG and ILG in age-related diseases to establish new therapeutics to improve human health and lifespan.